Sistema de Comercialización y su Incidencia en el Desarrollo de la Empresa Pública Municipal de Transformación y Comercialización de Productos Agrícolas Tierras Altas de la Ciudad de Cajabamba Provincia de Chimborazo Período 2015-2016 - Guamán Chiro, María Carmen (2019)
The present research was carried out to determine how the marketing system affects the development of the Municipal Public Company of Transformation and Commercialization of agricultural products “Tierras Altas” of de city of Cajabamba province of Chimborazo in the term 2015-2016. The present work consists of the following four chapters; thus: the first chapter contains the framework that is composed. Of the introduction, problem formulation, justification, general and specific objectives. The second chapter includes the theoretical framework which composed of the State of Art (background), theoretical foundation divided into three units, thus generalities of the company “Tierras Altas” marketing system and business development. the third chapter is detailed what refers to the methodological framework that is composed of the method that was used, type of research that was carried out, design, population and sample for the collection of information for the present investigation. The fourth chapter consists of the results of the survey, analysis, and interpretation of the same and the discussion of the results. The fifth chapter contains the conclusions and recommendations of the investigation, evidencing the results to the problems raised at the beginning of the present research. And the sixth chapter was considered a proposal for the “Tierras Altas” Company, for which it is necessary to determine marketing system strategies that allow business development